2014
DOI: 10.12980/apjtb.4.2014c1037
|View full text |Cite
|
Sign up to set email alerts
|

Screening, isolation and optimization of anti–white spot syndrome virus drug derived from marine plants

Abstract: The drug MP07X derived from Rhizophora mucronata is a potent anti-WSSV drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…Further, it can be said that with 1000 mg/kg of body weight/day of MP07X through oral increased the survival rate of vannamei shrimp up to of 85%. The previous report stated that MP07X was not toxic to shrimp against WSSV at an effective doses (Chakraborty & Ghosh, 2013b).…”
Section: The Mortality Of Tiger Shrimpmentioning
confidence: 94%
“…Further, it can be said that with 1000 mg/kg of body weight/day of MP07X through oral increased the survival rate of vannamei shrimp up to of 85%. The previous report stated that MP07X was not toxic to shrimp against WSSV at an effective doses (Chakraborty & Ghosh, 2013b).…”
Section: The Mortality Of Tiger Shrimpmentioning
confidence: 94%
“…Pemanfaatan mangrove sebagai antibakteri pada udang putih dan ikan hias juga telah dilaporkan (Arivuselvan et al, 2011;Dhayanithi et al, 2013), dan pada ikan mas (Ahilan et al, 2010). Selain sebagai anti bakteri, tanaman herbal mangrove dan asosiasinya juga mulai dikaji sebagai anti WSSV pada udang (Sahu et al, 2012;Chakraborty & Ghosh, 2013a, 2013b.…”
Section: Pendahuluanunclassified
“…However, as invertebrates, shrimp lack an adaptive immune system, rendering vaccination ineffective. As a result, many antiviral approaches that have been studied rely on enhancing host innate immunity [ 2 ]; examples include oral administration of probiotics [ 3 ], peptidoglycans [ 4 ] of β-glucan [ 5 ] and plant or seaweed extracts [ 6 ]. Other studies revealed that shrimp was capable of deploying an antiviral immune response via the RNA interference (RNAi) pathway [ 7 , 8 ], as evidenced by the finding that injection of double-stranded RNA (dsRNA) constructs with sequences that matched viral mRNA was effective in preventing viral diseases or reducing their severity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%